African Violets - Sydney Park Brown (EDIS)
Revised! ENH-17, a 3-page illustrated fact sheet by Sydney Park Brown, describes this popular house plant that grows and flowers under light conditions found in the average home, including requirements for lighting, temperature and humidity, soil and pots, watering, fertilizer, propagation and pest management. Includes references. Published by the UF Department of Environmental Horticulture, July 2007.